(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The current paper presents the new rock-cut assemblage of Pico de San Gregorio, set at the highest peak of Sierra de Santa Cruz, reflecting about its characteristics and its location in the landscape. It is also re-ferred the sites of Las Calderonas and San Cristóbal, included within the same geographical territory. Santuario Rupestre